Efeito do fosfopeptídeo de caseína-fosfato de cálcio amorfo (cpp-acp) no controle da erosão do esmalte dentário. - Diniz, Luciana Vilar de Oliveira (2011)
The objective of this study was to evaluate the effect of CPP-ACP in dental erosion control. For this purpose two studies. (1) The objective the first study was to evaluate in vitro the effect of pastes containing CPP-ACP and fluoride dentifrice in controlling dental erosion with or without abrasion. Eighty enamel blocks were divided into 10 groups (n = 8) according to the type of product used: MI Paste ® (G1/G6), Mi Paste Plus ® (G2/G7), Sensodyne Pro-Enamel ® (G3 / G8), Crest ® (G4/G9) and artificial saliva (G5/G10) and the experimental procedure: erosion with dripping with solution of the product (G1-G5) and erosion abrasion with dripping of the solution of the product (G6- G10). The specimens were subjected to simulated erosion using a soft drink as an agent of erosion, for three cycles of erosion of five minutes under constant agitation, for ten days. The surface roughness (Ra) was used to quantify the changes of the enamel surface eroded. For qualitative assessment of enamel was used SEM. There was a statistically significant difference (p <0.05) between groups G1-G4 in the control group G5 after the erosive challenge. The same occurred between groups G6-G9 and G10 when the erosion control was followed by abrasion. However, the products did not differ when they were compared in two conditions of erosion. In the evaluations of the SEM observed change in the surface of all experimental groups compared to healthy surface in each specimen surface. It can be concluded that the CPP-ACP and CPP-ACPF, showed ability to reduce the deleterious effects of erosion similar to fluoride toothpastes. (2) The objective of the second study was to evaluate in situ the effect of CPP-ACP incorporated into a chewing gum in reducing the increase of surface roughness of enamel after being subjected to erosive challenge with or without abrasion. This study presented a blind crossover design in which eight volunteers used intraoral palatal appliances containing six specimens. Each volunteer was subjected to three experimental periods of seven days each, with seven-day wash out between them. In each period were observed three conditions of erosion: erosion only, immediate erosion associated with brushing and erosion associated with brushing after an hour. The surface roughness (Ra, Rz and Rt) was used to analyze the surface changes. In all specimens there was an increase in roughness of enamel after the erosive challenges. Statistically significant difference was found between the experimental periods "no gum" and "gum with CPP-ACP" when erosion was followed by immediate brushing: Rz (p = 0.0148) and Rt (p = 0.036) and one hour after brushing Ra (p = 0.0312), Rz (p = 0.0264) and RT (p = 0.498). Among the three conditions of erosion in each period, the roughness values always followed the same pattern of presentation: erosion <erosion with abrasion after an hour <erosion with abrasion immediately, but there was no statistically significant difference. The data suggest that the use of chewing gum with CPP-ACP after ingestion of erosive beverages, contributes to reduction of dental enamel erosion, especially when the challenge is followed by the erosive abrasion. Thus, it is concluded that the CPP-ACP incorporated into folders or chewing gum was able to reduce the deleterious effects of dental erosion.